Metabolic routing maintains the unique fatty acid composition of phosphoinositides. (16th June 2022) - Kim, Yeun Ju; Sengupta, Nivedita; Sohn, Mira; Mandal, Amrita; Pemberton, Joshua G; Choi, Uimook; Balla, Tamas
Abstract: Phosphoinositide lipids (PPIn) are enriched in stearic‐ and arachidonic acids (38:4) but how this enrichment is established and maintained during phospholipase C (PLC) activation is unknown. Here we show that the metabolic fate of newly synthesized phosphatidic acid (PA), the lipid precursor of phosphatidylinositol (PI), is influenced by the fatty acyl‐CoA used with preferential routing of the arachidonoyl‐enriched species toward PI synthesis. Furthermore, during agonist stimulation the unsaturated forms of PI(4, 5P)2 are replenished significantly faster than the more saturated ones, suggesting a favored recycling of the unsaturated forms of the PLC‐generated hydrolytic products. Cytidine diphosphate diacylglycerol synthase 2 (CDS2) but not CDS1 was found to contribute to increased PI resynthesis during PLC activation. Lastly, while the lipid transfer protein, Nir2 is found to contribute to rapid PPIn resynthesis during PLC activation, the faster re‐synthesis of the 38:4 species does not depend on Nir2. Therefore, the fatty acid side‐chain composition of the lipid precursors used for PI synthesis is an important determinant of their metabolic fates, which also contributes to the maintenance of the unique fatty acid profile of PPIn lipids. Synopsis: This study describes how the unique fatty acyl side‐chain profile of phosphatidylinositol and phosphatidylinositol 4, 5‐bisphosphate are maintained during activation of phospholipase C and suggests that the metabolic fate of phosphatidic acid within the ER may be different depending on whether it is synthesized de novo or generated as the result of PLC or PLD activation. Utilization of fatty acyl‐CoA for de novo phospholipid synthesis or lipid storage depends on the chain length and unsaturation. PLC‐mediated PI(4, 5)P2 hydrolysis leads to increased PI synthesis that requires CDS2, but not CDS1 or DGKε. Resynthesis of PI(4, 5)P2 during PLC activation is faster for species containing unsaturated fatty acids. Abstract : This study describes how the unique fatty acyl side‐chain profile of phosphatidylinositol and phosphatidylinositol 4, 5‐bisphosphate are maintained during activation of phospholipase C and suggests that the metabolic fate of phosphatidic acid within the ER may be different depending on whether it is synthesized de novo or generated as the result of PLC or PLD activation.